ANALISIS SAMBUNGAN LAS GMAW BAJA ASTM A36 YANG TERPAPAR PANAS TINGGI DAN PENDINGINAN CEPAT - Nurudin Nurudin; Alfi Tranggono Agus Salim; Indarto Yuwono; Amelia Rahmatika; Suparman Suparman (Jurnal Teknologi Terapan, 2022)
Fires in steel construction, especially in welding joints, cause damage, changes in crystal structure, and mechanical properties of the material. Another effect of the fires, the material undergoes rapid cooling due to extinguishing using water. This research aims to simulate fires on ASTM A36 steel material to analyze the impact of fires. The method of this research is to perform GMAW welding on A36 steel material with heat treatment at 400 °C unti 700 °C and rapid cooling using water. The results of the research are the mechanical properties of the material in the form of crystal structure, hardness level and ultimate tensile strength. The crystal structure of ferrite and pearlite was observed, there was a change in structure, namely coarse ferrite, fine ferrite, and a mixture of bainite martensite. The highest hardness values of coupons temperature is 550 °C until 700 °C, comparison coupons, and coupons temperature at 400 °C-550 °C, which value 169,3 HV, 166.3 HV, and 141,3 HV in the weld zone. Tensile test fractures on the base metal with the ultimate tensile strength coupon with temperature 550 until 700 °C of 481,75 N/mm², the comparison coupon of 478,5 N/mm², and the temperature coupon of 400 until 550 °C which is 456 N/mm². The material is ductile.